PEMAHAMAN KONSEP PAJAK PADA ZAKAT - Pravitasari, Dyah (IAIN Tulungagung, 2016)
The purpose of this paper is to provide an overview of the similarities and differences in the concept of zakat and tax, opinions of the scholars concerning zakat and taxes, as well as explaining about the effective management of zakat based on the application of the concept of tax. The findings in this paper indicate that the similarities between the concepts of zakat and the concept of the tax, namely that both have the elements of force and manager. Meanwhile the differences are that two concepts are located on the side of the name, the Â legal basic, object, the nature of its obligations, the percentage of the amountpaid, and utilization. The concept of tax which can be applied in order to obtain effective management of zakat is to impose sanctions on manager of zakat and negligent muzzaki not pay their zakat as on tax management. This sanction will improve the system of zakat administration and establishmentof an independent agency that acts as the auditor.Keywords: Zakat, Tax, Similarities, Differences